Computational modelling of freezing of water droplet impacting on an ice surface. (2021) - Dash, Adarsh; Kumar Sahoo, Ashok; Yadav, Anshul; Patel, Virendra
Abstract: This study presents the computational modelling of freezing of water droplet on the ice surface. In this study, the transient fluid dynamics and heat transfer of the droplet during impact are considered. The governing equations for fluid flow are solved numerically using pressure–velocity coupling SIMPLE algorithm. The energy equation is modeled using an enthalpy-based formulation. The continuum surface flow model is used for modelling of surface tension. The model is endorsed with the experimental result from the literature by validating droplet spreading factor. The result shows that modelling of a droplet impacting on a surface with a suitable contact angle is very important. The results predicted from the present model are very much similar to the experimental results. Also, it is found that the high impact speed leads to more spreading of the droplet, which increases the surface area contact.